Ghana Strategy Support Program (GSSP) - International Food Policy Research Institute (International Food Policy Research Institute, 2007)
The Ghana Strategy Support Program (GSSP) website is a medium for circulating information relevant to Ghana's agriculture policy and strategy development. The blog contains updates on GSSP's work - ongoing research, upcoming events, publications, findings - as well as general information to support agricultural researchers and policymakers.